Variation in adult body mass of roe deer: early environmental conditions influence early and late body growth of females. Issue 8 (1st August 2013) - Douhard, Mathieu; Gaillard, Jean-Michel; Delorme, Daniel; Capron, Gilles; Duncan, Patrick; Klein, François; Bonenfant, Christophe
Abstract : There is increasing evidence that environmental conditions experienced early in life can markedly affect an organism's life history, but the pathways by which early environment influences adult phenotype are poorly known. We used long‐term data from two roe deer ( Capreolus capreolus ) populations (Chizé and Trois‐Fontaines, France) to investigate the direct and indirect (operating through fawn body mass) effects of environmental conditions during early life on adult body mass. We found that environmental conditions (population size and spring temperatures) around birth influenced body mass of adult females through both direct and indirect effects in both populations. The occurrence of direct effects means that, for a given fawn body mass, adult female mass decreases with adverse conditions in early life. In contrast, we found no evidence for direct effects of early‐life conditions on adult body mass of males, suggesting the existence of sex‐specific long‐term responses of body mass to stressful early conditions. Our results provide evidence that early environmental conditions influence the adult phenotype through persistent effects over the body development in wild mammal populations.